2015
DOI: 10.3390/toxins7093608
|View full text |Cite
|
Sign up to set email alerts
|

Ochratoxin A Dietary Exposure of Ten Population Groups in the Czech Republic: Comparison with Data over the World

Abstract: Ochratoxin A is a nephrotoxic and renal carcinogenic mycotoxin and is a common contaminant of various food commodities. Eighty six kinds of foodstuffs (1032 food samples) were collected in 2011–2013. High-performance liquid chromatography with fluorescence detection was used for ochratoxin A determination. Limit of quantification of the method varied between 0.01–0.2 μg/kg depending on the food matrices. The most exposed population is children aged 4–6 years old. Globally for this group, the maximum ochratoxin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
23
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 86 publications
6
23
1
2
Order By: Relevance
“…As cereals are widely used in animal feed, animals are potentially exposed to OTA through the consumption of contaminated feed, which can lead to the accumulation of this mycotoxin in meat and meat products (EFSA, 2004). Ranging OTA levels of 0.1-1 µg/kg have been detected in foodstuffs of animal origin (pork and chicken meat, dry-cured ham) (European Union, 2002;EFSA, 2004;Ostry et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…As cereals are widely used in animal feed, animals are potentially exposed to OTA through the consumption of contaminated feed, which can lead to the accumulation of this mycotoxin in meat and meat products (EFSA, 2004). Ranging OTA levels of 0.1-1 µg/kg have been detected in foodstuffs of animal origin (pork and chicken meat, dry-cured ham) (European Union, 2002;EFSA, 2004;Ostry et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Its occurrence was reported in Brazil [14], South Africa [18], Iran [21,22], Turkey [23], China [24], Japan [25], and Europe [13,20]. Namely, European studies reported it in Germany [26], Belgium [17], Spain [2], Italy [21,27], and the Czech Republic [19,28].…”
Section: Introductionmentioning
confidence: 99%
“…OTA possesses immunotoxic, nephrotoxic, embryotoxic, teratogenic, hepatotoxic, genotoxic, neurotoxic, and carcinogenic effects. Moreover, OTA has a long half-life (about 35 days) in human serum, meaning that it cannot be eliminated quickly from the plasma [1][2][3][4][5]. All of these factors make OTA among the most interesting of mycotoxins.…”
Section: Introductionmentioning
confidence: 99%